(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The purpose of the study is to find out the A Study of Relationship between Study Habits with Adjustment and its Dimensions of Rural and Urban Secondary School Students. The sample of the present study includes 200 secondary school students of Gokak. The sample were randomly selected from the population base gender and locality of the schools. Descriptive method was applied for the study. From the findings it is concluded that There is a positive and significant relationship between all the variables of adjustment and Study Habits of rural students. There is a positive and significant relationship between all the variables of adjustment and Study Habits of urban students studying in different secondary schools.